A useful tool for the safe diagnosis and control of the two main pandemics of the XXI century: COVID-19 and African Swine Fever disease - Barroso-Arévalo, Sandra; Díaz-Frutos, Marta; Kosowska, Aleksandra; Pérez-Sancho, Marta; Domínguez, Lucas; Sánchez-Vizcaíno, José Manuel (PLOS ONE, 2023)
The COVID-19 pandemic and the disease triggered by the African Swine Fever virus are currently two of the main problems regarding public and animal health, respectively. Although vaccination seems to be the ideal tool for controlling these diseases, it has several limitations. Therefore, early detection of the pathogen is critical in order to apply preventive and control measures. Real-time PCR is the main technique used for the detection of both viruses, which requires previous processing of the infectious material. If the potentially infected sample is inactivated at the time of sampling, the diagnosis will be accelerated, impacting positively on the diagnosis and control of the disease. Here, we evaluated the inactivation and preservation properties of a new surfactant liquid for non-invasive and environmental sampling of both viruses. Our results demonstrated that the surfactant liquid effectively inactivates SARS-CoV-2 and African Swine Fever virus in only five minutes, and allows for the preservation of the genetic material for long periods even at high temperatures such as 37°C. Hence, this methodology is a safe and useful tool for recovering SARS-CoV-2 and African Swine Fever virus RNA/DNA from different surfaces and skins, which has significant applied relevance in the surveillance of both diseases.